Synthesis, identification and application of the novel metal-organic framework Fe3O4@PAA@ZIF-8 for the drug delivery of ciprofloxacin and investigation of antibacterial activity - Maryam Esfahanian; Mohammad Ali Ghasemzadeh; Seyyed Mohammad Hossein Razavian (Artificial Cells, Nanomedicine, and Biotechnology)
Today, metal-organic frameworks (MOFs) for the release of drugs have been studied extensively. In this research, we have investigated the novel magnetic framework including Fe3O4@PAA@ZIF-8 for the delivery of ciprofloxacin (CIP) antibiotic. Moreover, the antibacterial activity of Fe3O4@PAA@ZIF-8 and Fe3O4@PAA@ZIF-8@CIP screened against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) bacteria. The structure of the nano carrier, as well as the encapsulation of the drug in the framework was confirmed by the Fourier-transform infrared spectroscopy (FT-IR), Ultraviolet–visible spectroscopy (UV–Vis), Energy-dispersive X-ray spectroscopy (EDX), X-ray crystallography (XRD), Scanning electron microscope (SEM) and Brunauer–Emmett–Teller (BET) analysis. The results of this study showed that 93% of the CIP was loaded on the synthesized framework. Drug release was done at pH: 7.4 and pH: 5 within 2 d, resulting about 73% release of the drug.